THE STATIONARITY OF ELECTRICITY CONSUMPTION IN SELECTED EUROPEAN COUNTRIES - Suleyman Bolat; Murat Belke; Sureyya Kovaci (European Scientific Journal, ESJ, 2013)
This study explores the stationary process of electricity consumption per capita for 16 European countries over 1960-2009 period using the individual unit root test (KPSS) with structural breaks developed by Carrion-i-Silvestre et al. (2005).This test allows for cross-sectional dependence and multiple structural breaks in both intercept-no trend and intercept-trend models. The results of individual KPSS tests with intercept-no trend show the null hypothesis of stationarity cannot be rejected except Belgium, France, Germany, Greece, Luxembourg, and Sweden. On the other hand, KPSS tests with intercept-trend indicate that the stationarity of electricity consumption per capita cannot be rejected except Luxembourg. Empirical results illustrate that the electricity consumption per capita is stationary process for almost all countries. These results reveal that any shock to electricity consumption per capita has a temporary effect for 15 countries, meaning that electricity consumption will return to its time trend. The stationary characteristic of electricity consumption is vital for forecasting electricity demand in response to exogenous shocks. As a result, the stationarity of electricity consumption per capita is important for forecasting and demand modeling of energy consumption.